Bio-waste sunflower husks powder based recycled triboelectric nanogenerator for energy harvesting. (November 2021) - Shaukat, Rayyan Ali; Saqib, Qazi Muhammad; Khan, Muhammad Umair; Chougale, Mahesh Y.; Bae, Jinho
Abstract: Sunflower seed is a popular food, but plenty of bio-waste sunflower husks are discharged into the world. If this bio-waste trash can be recycled, it will be reduced not only environmental pollution but also the waste of resources. In this paper, a triboelectric nanogenerator (SFP-TENG) based on a bio-waste sunflower husk powder is proposed and its open-circuit voltage, short circuit current, and instantaneous power are archived as 488 V, 28. 5 μ A, and 1200 μ W, respectively, under the frequency of 10 Hz with the excitation force of 58 N. The proposed SFP-TENG can harvest the biomechanical energy from the human body's daily motions. The fabricated SFP-TENG device is capable of lighting up 153 commercial LEDs. Furthermore, the SFP-TENG device is also tested under various humid environments such as 38, 49, 60, 79, and 89% relative humidity. Additionally, it can power up microelectronic devices such as calculator and stopwatch. Hence, we are sure that the proposed device can promote cost-effective and eco-friendly green energy harvesting through recycling bio-wastes as sunflower husk.